The common law principle of universality extended In the wake of Hanjin Shipping’s insolvency - WATTERS, Casey Gene (Institutional Knowledge at Singapore Management University, 2018)
The SingaporeHigh Court decision in Re Taisoo Suk is a notable developmentof the law on cross-border insolvency for two reasons. First, the decision hasimplications on the relationship between the admiralty jurisdiction inSingapore and the Singapore court’sinherent powers in the context of cross-border insolvency. Second, it is the most recent in aseries of cases breaking from Rubin v Eurofinance SA and developingSingapore’s common law authority to assist foreign insolvency proceedings. WhileSingapore subsequently adopted the UNCITRAL Model Law on Cross-Border Insolvency, the increased scope of the court’s inherent authority remains aflexible tool available to debtors and, whereas the Model Law’sadoption in the Companies Act does not extend to personal bankruptcy, the decisionpaved the way for common law recognition of foreign personal bankruptcyproceedings.The case also establishes persuasive precedent for jurisdictions seeking to adopta more flexible common law approach.Whereas previousdecisions have already recognized the court’s authority to remit assets for distributionin main proceedings, the decision in this case went even further: itestablished a test for the recognition of insolvency proceedings, and allowedthe grant of an injunction within Singapore that was premised on the court’sinherent jurisdiction to assist foreign insolvency proceedings and which alsoextended to the subsidiaries of the insolvent company, thereby ignoring thesubsidiaries’ separate legal identities. The ramifications and possiblerationales of these developments will be discussed subsequently in this note.